(untitled) (Itinera, 2020)
Christopher Norris is Emeritus Professor of Philosophy at Cardiff University. He worked on literary criticism, on the question of realism and antirealism in philosophy, on Derrida and deconstructionism and on the philosophy of science. In the past few years he has also authored several philosophical poems. In this issue we present two poems he wrote that are dedicated to color.